The Roles of Islamic Education in Building Self-Regulated Learner in the Era of Distance Education - Fitrianto, Hanif (At-Ta’dib, 2020)
The pandemic of corona virus covid-19 has changed various aspects of life, both politically, culturally, economically and educationally. To avoid the spread of this epidemic from becoming more widespread, the government decided to shift the classical learning model to distance learning. With its various weaknesses, self-regulated learning becomes a solution to strengthen students’ motivation and achievement of learning goals. This study was conducted to find a relationship between the role of Islamic religious education and self-regulated learning. Through literature research with a descriptive analysis approach, the results show that Islamic religious education can play a role in: 1) strengthening students’ self-control in the learning process, 2) building learning motivation with various media in accordance with Islamic teachings, 3) building learning goals oriented to the goodness of the world and the afterlife